2005
DOI: 10.1002/mrc.1668
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and structure in the Mn2+ site of concanavalin A as determined by high-field EPR and ENDOR spectroscopy

Abstract: The properties of the Mn2+ site in the protein concanavalin A were investigated by single crystal W-band EPR/ENDOR (electron-nuclear double resonance) measurements. Initially, room temperature EPR measurements were carried out, one type of Mn2+ was identified and its zero-field splitting (ZFS) tensor was determined. In contrast, low temperature EPR measurements showed that two chemically inequivalent Mn2+ are present, Mn(A)2+ and Mn(B)2+, differing in their ZFS tensors. Variable temperature measurements reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…The EPR settings are the same as described in the main text. Mn 2+ has two characteristic peaks located the RF of ~114 MHz, ~158 MHz and at 375 MHz (not shown) under these experimental conditions described in Figure caption 2, see also ref[6][7][8] .…”
mentioning
confidence: 74%
“…The EPR settings are the same as described in the main text. Mn 2+ has two characteristic peaks located the RF of ~114 MHz, ~158 MHz and at 375 MHz (not shown) under these experimental conditions described in Figure caption 2, see also ref[6][7][8] .…”
mentioning
confidence: 74%
“…More precisely, there was negligible distribution in the proton hyperfine interactions, in particular the dipolar couplings, which are determined by the Mn–H distances. Studies on single crystals of ConA have shown that the manganese ions occupy two sites that have different zero-field interactions ( D = 789 and E = 189 MHz and D = 970 and E = 140 MHz) but the same proton ENDOR spectra, as well as 55 Mn quadrupole tensors. , This suggested that the Mn II zero-field interactions are more sensitive than the other magnetic interactions to local structure disorder or, more likely, to nonstructural effects. Electrostatics originating from well beyond the primary ligand sphere have been shown to affect the Mn II zero-field interaction with little or no change to the structure of the ligand sphere. , Therefore, it seemed likely that large zero-field distribution of the imidazole complexes originated from the disorder in the surrounding ions that did not affect the structure of the manganese imidazole complex.…”
Section: Resultsmentioning
confidence: 99%
“…However, conventional EPR has proven to be of limited value due to poor resolution and high spectral complexity. Recently, several experiments have been carried out using high magnetic-field high-frequency EPR (HFEPR) that suggest that this approach not only circumvents these two limitations but also allows accurate measurement of the magnetic spin parameters of an Mn(II) ion from which valuable information about its electronic structure and interactions with the environment can be extracted.…”
Section: Introductionmentioning
confidence: 99%